Hubungan Antara Ekonomi dengan Lingkungan Hidup: Suatu Kajian Literatur - Ria Armayani, Reni; Kholilah Lubis, Hilma; Sari, Novita (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2022)
Economic activities carried out by humans affect the surrounding environment. Economic activities by utilizing resources for production and consumption can have both positive and negative impacts on human life. The positive impact that can be directly felt is the fulfillment of the need for goods and services which are strived to continue to increase from year to year. More goods and services being produced and consumed indicates an increase in people's prosperity. Negative impacts are generally not felt directly, namely the emergence of pollution and environmental damage. As a result of environmental pollution reduces the quality of human life which can interfere with daily life. The research method used in this research is library research method. The results show that environmental sustainability is something that is non-negotiable to ensure the economic needs of the present generation without compromising the carrying capacity of the environment for future generations. Protecting the environment is not only needed to limit pollution, but also to ensure eco-efficiency in meeting the needs of the current generation. From the discussion in this research, it can be seen that polluters are not only limited to companies and other individuals, but also the government, for example.